Rancang Bangun Aplikasi Jasa Pengiriman Pos Pada PT Pos Indonesia - Maharddhika, Rendy; Wurijanto, Tutut; Ayuningtyas, Ayuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Pos Indonesia is a company engaged in postal service. PT Pos Indonesia has a vision that is to become the trusted postal companies. Business process activities of shipping packages at PT Pos Indonesia starts from senders hand over a package in the post office counter until accepted by the recipient. But many packages failed to delivered to the recipient due to lack of information of the recipients of a courier who will come to deliver the package. In addition, the process of contacting the recipients is done manually by the phone. The other problem is when there is a failed package delivered, then the courier must take back the package to the recipient. Redeliver activities caused the rising cost of the delivery process. This application is built to resolve the problems of shipping process at PT Pos Indonesia. This application can provide notification of the existence of the package to the sender by email and give a notification of the existence of the package to the recipient via SMS. With this application is expected an increase in performance at PT Pos Indonesia and could solve existing problems.